Analisis Pengaruh Kompensasi, Gaya Kepemimpinan Dan Kepuasan Kerja Terhadap Kinerja Pegawai Di Sekretariat Daerah Kota Manado - Tewal, Otniel K (Universitas Sam Ratulangi, 2015)
the theory that used in this research is human resources management theory, especially the aims of this research areÂ To know the influence of compensation, leadership style And job satisfaction towards the performance of the workers in the Regional Secretariat Of Manado City. The type of the research is associative research. The location of the research is the Regional Secretariat Of Manado City. The Population of this research is all employees in the Regional Secretariat Of Manado City in the amount of 201 with 127 decided as respondents. The data analaysis is using multiple linear regression. Conclusion compensation and job satisfication variable influence towards the performance of the workers. Keywords: Compensation, Leadership Style, Job Satisfaction and Performance